Investigating the Impact of Caraway Extract on Metabolic Disorders in Male Rats with Induced Hypothyroidism - Hamed , Ahmed; Majeed Mohamed Ali, Sabreen (Hammurabi Journal of Medical Sciences, 2024)
Background: Methimazole-induced hypothyroidism is a frequently used model for investigating thyroid dysfunction and the metabolic problems that accompany it. Conventional therapies, such as levothyroxine, are efficacious but might potentially cause adverse reactions. Caraway extract, derived from the Carum Carvi plant, is recognized for its antioxidant and anti-inflammatory characteristics. It has demonstrated promise in reducing these effects. Objectives: This study assesses its influence on thyroid hormone levels, weight gain, and blood glucose levels. Materials and Methods: Forty male Wistar rats were categorized into four groups. The control group (G1) did not receive any intervention or treatment. Group 2, referred to as the hypothyroid group, was intentionally administered methimazole to cause hypothyroidism. Group G3, referred to as the Caraway extract group, was administered caraway extract following the development of hypothyroidism. The positive control group (G4) was administered levothyroxine following the establishment of hypothyroidism. The diagnosis of hypothyroidism was confirmed by assessing reduced levels of free thyroxine (fT4) and free triiodothyronine (fT3), in addition to high thyroid-stimulating hormone (TSH). The efficacy of the treatments was assessed by comparing these metrics across the different groups. Results: The administration of caraway extract (G3) led to notable enhancements in thyroid hormone levels, characterized by increased concentrations of fT4 and fT3 and decreased levels of TSH compared to the hypothyroid group (G2). In addition, caraway extract effectively lowered blood glucose levels and facilitated weight gain, indicating improved metabolic health and glucose regulation. Conclusions: It could be concluded that caraway extract can successfully alleviate the effects of methimazole-induced hypothyroidism. These findings indicate that caraway extract may be a promising adjunct therapy for the management of hypothyroidism and associated metabolic problems.